Lonicera lanzhouensis (Caprifoliaceae), a new species from Gansu, Northwest China - Shun Liu; Yu-Jin Wang (PhytoKeys)
Lonicera lanzhouensis (Caprifoliaceae), a new species from Lanzhou City, Gansu province, China, is described and illustrated. The new species is morphologically similar to L. webbiana in that it has a bilabiate corolla and a long peduncle. It differs by narrowly lanceolate leaves (vs. ovate to ovate-lanceolate), yellow-green corolla at the beginning and reddish-purple when mature (vs. purple-red) and long involucral bracts (vs. short). The new species is supported by the genetic differentiation and phylogenetic analysis based on ITS and the combined sequences of chloroplast psbA-trnH and matK fragments.